Decreasing the Supply of and Demand for Guns: Oakland’s Youth Advocacy Project - Calhoun, Deane (Springer US, 2013)
This paper is a case study of how Youth ALIVE!, a nonprofit public health organization, blended direct service and policy goals to reduce youth gun violence at a time when guns became the number one killer of children in California. Youth ALIVE! trained young people living in California communities with the highest rates of gun violence to become peer educators and leaders to reduce both the supply of, and demand for, guns. The youth presented health and criminal justice data in the context of their own experiences living in communities endangered by gun violence to help build public policy solutions, contributing to the subsequent drop in gun homicides. Youth ALIVE’s vibrant grassroots model provides a real-life tableau of research and direct services working together to yield realistic policy solutions to a lethal public health problem. The youths’ successes demonstrate how nonprofit direct service organizations are uniquely positioned to advocate for policy and regulatory changes that can be beneficial to both program participants and society. Direct service organizations’ daily exposure to real-life client needs provides valuable insights for developing viable policies—plus highly motivated advocates. When backed by scientific findings on the causes of the problem, this synergy of youth participant engagement in civil society can promote good policy and build healthy communities.